Concentric left ventricular remodelling is associated with subclinical systolic dysfunction in patients with psoriatic arthritis. (2nd September 2020) - Giollo, A; Farina, N; Cioffi, G; Ognibeni, F; Dalbeni, A; Orsolini, G; Idolazzi, L; Gatti, D; Rossini, M; Viapiana, O
Abstract : Objectives : Subclinical left ventricular (LV) abnormalities have been reported in echocardiographic studies of patients with psoriatic arthritis (PsA). Left ventricular systolic dysfunction (LVSD) often coexists with concentric LV remodelling, an unfavourable prognostic factor that is commonly found in patients at high cardiovascular risk. However, it is unclear whether PsA is associated with concentric LV remodelling. This cross-sectional study assesses the prevalence of and factors associated with concentric LV remodelling in a cohort of patients with PsA, and tests the hypothesis that concentric LV remodelling is a major determinant of LVSD in PsA. Method : We evaluated 101 adults attending an outpatient clinic with PsA diagnosed according to the ClASsification criteria for Psoriatic ARthritis (CASPAR). All patients were free of cardiovascular disease. Patients with PsA were compared with 101 controls matched for age, gender, body mass index, hypertension, and diabetes. Echocardiography was performed: concentric LV remodelling was defined if the relative wall thickness was > 0.43; stress-corrected mid-wall shortening was used as an index of LVSD and considered impaired if < 86.5%. Results : Concentric LV remodelling was found in 58% of patients with PsA and 18% of controls (p < 0.001). LVSD was found in a significantly higher proportion of patients with PsA (56%, p < 0.001) than controls. The presence of PsA yielded a 10-fold higher probability of having LVSD [odds ratio (OR) 9.6, 95% confidence interval (CI) 4.2–21.9, p < 0.0001]. In patients with PsA, concentric LV remodelling increased the risk of LVSD four-fold (OR 3.7, 95% CI 1.3–10.2, p = 0.013). Conclusion : Most asymptomatic patients with PsA have concentric LV remodelling, which is closely associated with subclinical LVSD.